Guidelines Development for the Role of Administrators in Safety School under the Secondary Educational Service Area Office Bangkok 1 - Makate, Prathan; Suthiyam, Urai (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2025)
The objective of this research were 1) to study the current state and desired state of the role of school administrators in managing a safe educational environment, and 2) to propose strategies for developing the role of administrators in managing a safe school. The research was divided into two phases: Phase 1 Study the current and desired states of the role of administrators in managing safe schools under the Secondary Educational Service Area Office 1 in Bangkok. Using Cohen et al.'s (2018, p. 206) table for the sample, 357 people were selected. The research instrument was a questionnaire, with a consistency index ranging from 0.10 to 0.70, and the reliability analysis (Cronbach's alpha) was .93 Statistical methods included mean, standard deviation (SD), and the analysis of the modified priority needs index (PNIModified). Phase 2 In-depth interviews with 7 experts. The findings of the research were as follows: The current state was considered to be at a high level, and the desired state is also at a high level. When considering the priority needs index (PNI-modified), the safety policy area was ranked the highest overall, with a PNIModified value of 0.172. The areas with the highest priority needs were safety policy (PNIModified = 0.198), participation (PNIModified = 0.182), and health and hygiene (PNIModified = 0.150), respectively. The strategies for developing the role of administrators in managing a safe school were : Participation: Administrators should assign roles to committees to participate in analyzing problems, assessing risks, ranking risks, and creating effective communication channels. Continuous monitoring and evaluation will help improve safety measures. Safety Policy: Administrators should develop clear safety policy documents and plans with 3 key measures. PDCA meetings, the use of online media, and training will promote participation and the monitoring of safety assessments. Health and Hygiene: Administrators should organize campaigns and create learning materials, such as guides and short videos, to enhance health and safety skills. Training and communication channels will promote awareness among students and staff. Prevention, Cultivation, and Enforcement: Administrators should train a rapid response team and prepare necessary equipment. Developing safety curricula and creating communication channels will enhance knowledge and awareness of safety.